Osteocalcin and Matrix Gla Protein in zebrafish (Danio rerio) and Senegal sole (Solea senegalensis): comparative gene and protein expression during larval development through adulthood - Gavaia, Paulo J. (2014)
Bone Gla protein (Bgp or osteocalcin) and matrix Gla protein (Mgp) are important in calcium metabolism and skeletal development, but their precise roles at the molecular level remain poorly understood. Here, we compare the tissue distribution and accumulation of Bgp and Mgp during larval development and in adult tissues of zebrafish (Danio rerio) and throughout metamorphosis in Senegal sole (Solea senegalensis), two fish species with contrasting environmental calcium levels and degrees of skeletal reorganization at metamorphosis. Mineral deposition was investigated in parallel using a modified Alizarin red/Alcian blue protocol allowing sensitive simultaneous detection of bone and cartilage. In zebrafish, bgp and mgp mRNAs were localized in all mineralized tissues during and after calcification including bone and calcified cartilage of branchial arches. Through immunohistochemistry we demonstrated that these proteins accumulate mainly in the matrix of skeletal structures already calcified or under calcification, confirming in situ hybridization results. Interestingly, some accumulation of Bgp was also observed in kidney, possibly due to the presence of a related protein, nephrocalcin. Chromosomal localization of bgp and mgp using a zebrafish radiation hybrid panel indicated that both genes are located on the same chromosome, in contrast to mammals where they map to different chromosomes, albeit in regions showing synteny with the zebrafish location. Results in Senegal sole further indicate that, during metamorphosis, there is an increase in expression of both bgp and mgp, paralleling calcification of axial skeleton structures. In contrast with results obtained for previously studied marine fishes, in zebrafish and Senegal sole Mgp accumulates in both calcified tissues and non-mineralized vessel walls of the vascular system. These results suggest different patterns of Mgp accumulation between fish and mammals.